Հայկական դատաստանագրքերի բառապաշարը միջնադարում - Մուշեղյան, Ա. Հ. (ՀՀ ԳԱԱ Հ. Աճառյանի անվ. լեզվի ինստիտուտ)
Армянские судебники средних веков включают многие термины, а также новшества среднеармянского языка. Здесь представляется лексика этих трудов в кратком содержании.Armenian codices of Middle Ages involve a great number of terms and innovations of the Middle Armenian language. Here we observe the vocabulary in brief.
Keywords: Լեզվաբանություն; Բառարանագրություն